Strategies to professionalize the presidential campaigns in Colombia during 1994-2014 [Estratégias de profissionalização das campanhas presidenciais na Colômbia desde 1994-2014] [Las estrategias de profesionalización de las campañas presidenciales en Colombia desde 1994-2014] (2019)
The purpose in this article is to analyze a growing modernization and adaptation of the American model to the presidential campaigns in Colombia from 1994 up to the campaigns in 2014. Any electoral process has some particular characteristics evincing the impact of the country s political system on both the internal and external organization of the electoral campaigns. These are structured based on the exploitation of professionalization techniques or factors aiming to gain the highest numbers of voters. To understand this phenomenon, the professionalization level of the presidential campaigns in Colombia will be measured by establishing some analysis categories allowing describing and comparing both the development and evolution of the techniques used in each campaign. All this would enable to compare the professionalization levels. © 2019 Pontificia Universidad Javeriana. All rights reserved.